Isolation and characterization of microsatellites for the neotropical dioecious palm Chamaedorea tepejilote (Arecaceae) and cross-amplification in other Chamaedorea species - Fuchs Castillo, Eric J. (2020)
Palms are important components of tropical and subtropical ecosystems and have even been considered keystone plant resources that can support a large array of pollinators and frugivores. Palms are also economically important. Chamaedorea tepejilote Liebm. is a widely distributed palm with important bioeconomic potential for food, traditional medicine and ornamental purposes. Eighteen microsatellite primers were developed for C. tepejilote. Polymorphism and genetic diversity were evaluated in 71 individuals from four populations in Costa Rica. Thirteen loci were polymorphic and the number of alleles in the pooled sample ranged between 5 and 20, the average number of alleles was 10.61. Average observed heterozygosity was Ho = 0.607 ± 0.04 (SD) and the average expected heterozygosity was He = 0.600 ± 0.03. The exclusion probability of the combined 13 loci, was PE = 0.998. We tested transferability of the markers in the congeneric C. costaricana, C. pinnantifrons and C. macrospadix. Dioecious species are common in tropical forests; however, few studies have analyzed gene flow patterns in these species. The markers developed for C. tepejilote are an important tool to quantify gene flow patterns and the distribution of genetic diversity within populations. This information will be useful for the development of conservation and management practices of this dioecious tropical palm species.